Effect of Pitch Distribution on The Propeller Efficiency and Cavitation of Offshore Patrol Vessels 98 Meter - Risnawan, Novan; Setyanto, Taufiq Arif; Gani, Erzi Agson; Indiaryanto, Mahendra; Adietya, Berlian Arswendo (Department of Naval Architecture - Diponegoro University, 2025)
This paper discusses the effect of pitch distribution on the propeller of a high-speed vessel (Offshore Patrol Vessel) on propeller efficiency and cavitation on the propeller blade surface. A propeller model design with five blades featuring symmetric blade contours and ogival-shaped foil, tested through open water tests in a towing tank, is used as the research object. Three variations of pitch distribution based on PropCAD recommendations: original pitch, 80% hub pitch distribution, and high-thrust pitch distribution, are used as parameters to calculate propeller efficiency using Computational Fluid Dynamics (CFD). The cavitation phenomena occurring on the propeller blades under each pitch distribution condition are analysed using the Burrill method (Burrill Diagram). Based on CFD analysis, it was found that the propeller with the highest propeller efficiency, η, is obtained from the high-thrust pitch distribution (0.6072), compared to the original pitch distribution (0.5902) and the 80% hub pitch distribution (0.5651). Cavitation occurs in all three pitch variations because the thrust loading coefficient values (τc) for the original pitch distribution (0.1286), 80% hub pitch distribution (0.1183), and high-thrust pitch distribution (0.1293) are higher than the cavitation threshold from the Burrill diagram (τ'c = 0.0783).